2010
DOI: 10.1111/j.1750-3841.2009.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Potent Anticariogenic Activity of Aceriphyllum rossii and Its Components, Aceriphyllic Acid A and 3‐oxoolean‐12‐en‐27‐oic Acid

Abstract: Aceriphyllum rossii Engler (Saxifragaceae) have been used as a nutritious food in Korea. We found that the methanol extract of A. rossii root and its components, aceriphyllic acid A and 3-oxoolean-12-en-27-oic acid, potently inhibited the growth of the key cariogenic bacteria, Streptococcus mutans, with MIC of 2 to 4 microg/mL. They also showed antibacterial activity against other cariogenic bacteria such as S. oralis, S. sobrinus, and S. salivarius with the similar potency. In the time-kill study, aceriphylli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A. rossii is a rich source of 12-en-27-oic acid-type triterpenes [ 31 , 32 , 33 ]. These triterpenes have a variety of biological effects including anticomplementary, cytotoxic, anti-bacterial, anti-cancer, anti-inflammatory, and diacylglycerol aceyltransferase-inhibitory activities [ 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. In the current study, we demonstrated that two 3-hydroxyolean-12-en-27-oic acid derivatives, AR-3 and AR-5, suppressed RANKL-induced osteoclast differentiation, actin-ring formation, and resorption pit formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. rossii is a rich source of 12-en-27-oic acid-type triterpenes [ 31 , 32 , 33 ]. These triterpenes have a variety of biological effects including anticomplementary, cytotoxic, anti-bacterial, anti-cancer, anti-inflammatory, and diacylglycerol aceyltransferase-inhibitory activities [ 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. In the current study, we demonstrated that two 3-hydroxyolean-12-en-27-oic acid derivatives, AR-3 and AR-5, suppressed RANKL-induced osteoclast differentiation, actin-ring formation, and resorption pit formation.…”
Section: Discussionmentioning
confidence: 99%
“…A. rossii is a rich source of 12-en-27-oic acid-type triterpenes [31][32][33]. These triterpenes have a variety of biological effects including anticomplementary, cytotoxic, anti-bacterial, anti-cancer, anti-inflammatory, and diacylglycerol aceyltransferase-inhibitory activities [26,[32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Both the extract were found to be bacteriostatic while malvidin-3,5-diglucoside, isolated from ethanol extract of flowers was found to be the principal constituent for antibacterial activity. In a study, Zheng et al (2010) observed inhibitory efficacy of methanol extract of Aceriphyllum rossii Engler root and its components aceriphyllic acid A and 3-oxoolean-12-en-27-oic acid against all cariogenic bacteria tested. Aceriphyllic acid A was found to possess faster bacteriostatic activity and the inhibitory action was shown to be membrane disruption leading to killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%